The Kurds of the Republic of Azerbaijan and the issue of Red Kurdistan - تونویان آرتیوم; میساکیان گاریک (The Scientific Journal of Cihan University– Sulaimaniya, 2022)
Although some political circles in Azerbaijan are currently trying to hide or distort the Kurdish issue and the historical presence of that people in the region, a study of historical facts, sources and documents shows that the Kurds had a significant political and social presence in Azerbaijan, especially in the 19th and 20th centuries. The Kurdish presence in the territory of present-day Azerbaijan and the Kurds’ movements in the South Caucasus in the 19th and 20th centuries were accompanied by important political and historical events. Although there is not much specific scientific works on the Kurds of Azerbaijan, however, studies of existing studies and documents and sources preserved from the Soviet era can reveal remarkable facts about the history of the Kurds of Azerbaijan and the area called "Red Kurdistan". The article uses the descriptive-analytical research method. Mainly used library literature, documentaries printed in Russian, dailies published in Soviet Azerbaijan, as well as official census data published by the Soviet and Russian Empire’s governments. The article attempts to study the historical, political and social presence of the Kurds in the Soviet Union and its predecessors in the territory of present-day Azerbaijan, as well as the political and social role of the Kurds in the region called "Red Kurdistan" and in the territory of the current NAR, to present the demographic picture of the Kurds in the above-mentioned territories and the policy of the governments of the Soviet and Democratic Republics of Azerbaijan towards the Kurds.